Fibroblast encapsulation in hybrid silica-collagen hydrogels - Desimone, Martín Federico (2010)
Silica-collagen scaffolds are synthesized by the simultaneous polymerization of aqueous silicates and self-assembly of protein triple helices in the presence of living human dermal fibroblasts.